The role of health and health systems in shaping political engagement and rebuilding trust in democratic institutions - Anil Menon; Nolan M. Kavanagh; Michelle Falkenbach; Matthias Wismar; Scott L. Greer (The Lancet Regional Health. Europe)
Summary: Around the world, institutional trust is declining while democratic discontent is rising. What role do health and health systems play in this crisis? We review decades of interdisciplinary research to describe how health and health systems are linked to democratic trust and engagement. When individuals or communities experience a decline in their health, they feel “let down” by the health system and other public institutions meant to support their well-being. Consequently, they are less likely to vote. Those who continue to vote are increasingly drawn to anti-establishment, anti-democratic parties that promise to radically reform the system. Once in power, however, these parties often weaken public health protections or exclude select populations from the health system. The result can be a self-reinforcing feedback loop between declining health and political discontent. We conclude by offering concrete suggestions for improving population health while rebuilding trust in health systems and democratic institutions more broadly.